Tiki Taka’s Strategy as an Effort to Prevent Copyright Infringement in Indonesia: E-Commerce Platforms on Digital Era - Ashibly, Ashibly; Jimmy, Fulgensius (PT. Riset Press International, 2024)
The spread of the internet in social life means that there are more and more violations of creations, it is difficult to identify anyone who commits violations, and it is not easy to protect a creation in digital form. If these violations are not addressed, they can have a negative impact on the industry and creators. Violations of the economic rights of creators and copyright holders in the form of digital products/creations have been generally and openly bought and sold on e-commerce platforms in Indonesia without any real action being taken against products that violate the economic rights of creators or copyright holders of the platform the e-commerce. The aim of this research is to find out the tiki taka strategy in preventing copyright infringement in the digital era on e-commerce platforms in Indonesia. The type of research in this research is empirical legal research. Empirical legal research is